Evaluation of Antimicrobial Activity OF Acalypha Indica Against Various Enteric Gut Pathogens - Richard Lobo (Journal of Global Pharma Technology, 2017)
The present study aimed to identify the photochemical constituents and possible microbicidal potential of ethanol and aqueous extract of Acalyphaindica leaf extract on various gut pathogens. Shade dried leaves of Acalyphaindicawere extracted with solvents of increasing polarity. In vitro anti microbial activity of the water and alcoholic extracts of A. indica was performed by agar punch well diffusion method on selected gut pathogens. Photochemical study of the extracts of A. indicareveals the presence of phytoconstituents like alkaloids, phytosterols, carbohydrates and gums and mucilage’s. Both the aqueous and ethanol extracts showed good to moderate activity against Plesiomonasshigelloide, Shigellaflexineri, Klebsiella pneumonia, Vibrio cholera and Staphylococcus aureus. From the about results we conclude that, the traditionally used medicinal plant A.indica can be useful against the disease causing gut pathogens Keywords: Antimicrobial activity, Acalyphaindica, Gut pathogens, Agar diffusion method, Photochemical screening.